Does health-related poverty publication landscape reflect global needs in the light of the current poverty rebound? - Doris Klingelhöfer; Markus Braun; Dörthe Brüggmann; David A. Groneberg (BMC, 2022)
Abstract Background After nearly a quarter-century of declining poverty, the numbers are rising again significantly. This is due not only to effects of climate change but also to the COVID-19 pandemics and armed conflict. Combined with the enormous health impacts, that will cause misery and health care costs worldwide. Therefore, this study provides background information on the global research landscape on poverty and health to help researchers, stakeholders, and policymakers determine the best way to address this threat. Results The USA is the key player, dealing mainly with domestic issues. European countries are also involved but tend to be more internationally oriented. Developing countries are underrepresented, with Nigeria standing out. A positive correlation was found between publication numbers and economic strength, while the relationship between article numbers and multidimensional poverty was negatively correlated. Conclusions These findings highlight the need for advanced networking and the benefits of cross-disciplinary research to mitigate the coming impacts.